Increased risk of rhinovirus infection in children during the coronavirus disease‐19 pandemic. Issue 4 (14th March 2021) - Takashita, Emi; Kawakami, Chiharu; Momoki, Tomoko; Saikusa, Miwako; Shimizu, Kouhei; Ozawa, Hiroki; Kumazaki, Makoto; Usuku, Shuzo; Tanaka, Nobuko; Okubo, Ichiro; Morita, Hiroko; Nagata, Shiho; et al.
Abstract: Background: Coronavirus disease (COVID‐19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), was first detected in Japan in January 2020 and has spread throughout the country. Previous studies have reported that viral interference among influenza virus, rhinovirus, and other respiratory viruses can affect viral infections at the host and population level. Methods: To investigate the impact of COVID‐19 on influenza and other respiratory virus infections, we analyzed clinical specimens collected from 2244 patients in Japan with respiratory diseases between January 2018 and September 2020. Results: The frequency of influenza and other respiratory viruses (coxsackievirus A and B; echovirus; enterovirus; human coronavirus 229E, HKU1, NL63, and OC43; human metapneumovirus; human parainfluenza virus 1, 2, 3, and 4; human parechovirus; human respiratory syncytial virus; human adenovirus; human bocavirus; human parvovirus B19; herpes simplex virus type 1; and varicella‐zoster virus) was appreciably reduced among all patients during the COVID‐19 pandemic except for that of rhinovirus in children younger than 10 years, which was appreciably increased. COVID‐19 has not spread among this age group, suggesting an increased risk of rhinovirus infection in children. Conclusions: Rhinovirus infections should be continuously monitored to understand their increased risk during the COVID‐19 pandemic and viral interference with SARS‐CoV‐2.